The effect of axial tension and borehole curvature on torsion limit of drill string threaded connections. (September 2021) - Chen, Feng; Huo, Yonghao; Zhao, Haiyi; Di, Qinfeng; Wang, Wenchang; Zhou, Xing; Zhang, Yun
Highlights: A new method for evaluating the torsion limit of threaded connections is proposed. The stress characteristics of threaded connections under complex loads is revealed. The effect of complex loads on the torsion limit of threaded connections is studied. The torsion limit of threaded connections can be determined easily with the 3D diagram. Abstract: Threaded connections of drill string have to withstand huge axial tension, large working torque, and even severe bending. When these loads exceed a certain value, threaded connections often fail and may lead to enormous losses. There is no formula for calculating the torsional capacity of threaded connections under complex loads, even in API standards. In this study, the stress characteristics of threaded connections under complex loads were analyzed with 3D elastic–plastic finite element mothed, and a new method was presented to determine the torsion limit of threaded connections under tension and bending. The results show that the torsion limit of threaded connections increases first and then decreases with the increase of axial tension, while decreases gradually with the increase of bending moment. The safety factor 1.1 in API Standard for bending moment is incomplete and a reasonable one can be determined by using the proposed method. The prediction model and 3D diagram allow engineers and operators to easily obtained torsion limit of threaded connections under arbitrary axial tension and borehole curvature.